The hammer of Thor - Riordan, Rick (Los Angeles : New York : Disney/Hyperion, 2016)
Just when Magnus thinks life at Hotel Valhalla has returned to normal, friends go missing, a hallmate is creating chaos, and a certain object belonging to Thor is still missing.
Keywords: Chase, Magnus (Fictitious character) -- Juvenile fiction; Mythology, Norse -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Homeless children -- Juvenile fiction; Fantasy fiction